2012
DOI: 10.1111/j.1464-410x.2012.11368.x
|View full text |Cite
|
Sign up to set email alerts
|

Tumour characteristics, oncological and functional outcomes in patients aged ≥ 70 years undergoing radical prostatectomy

Abstract: Study Type – Therapy (case series) Level of Evidence 4 What's known on the subject? and What does the study add? The marked increase in life expectancy in recent years calls for reconsideration of the decision‐making process for the treatment of prostate cancer, a condition particularly affecting the elderly. To date the general approach in elderly patients has tended to be more conservative, not least as it is generally thought that prostate cancer in these patients is less biologically aggressive. The presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
26
1
6

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 21 publications
4
26
1
6
Order By: Relevance
“…In the PIVOT study, 47.0% of patients (median age, 67 years) who underwent RP died during a median follow-up of 10 years. In the present study, the 5-year OS rate was 95.8% with the median age of 72 years among those 70 years of age, which was much better than that reported in the previous studies (3,12). Life expectancy in Japanese men is longer than that for men in other countries (4), and men under healthy conditions and less comorbidities would have undergone RP in our study.…”
Section: Rp In Elderly Mencontrasting
confidence: 49%
See 2 more Smart Citations
“…In the PIVOT study, 47.0% of patients (median age, 67 years) who underwent RP died during a median follow-up of 10 years. In the present study, the 5-year OS rate was 95.8% with the median age of 72 years among those 70 years of age, which was much better than that reported in the previous studies (3,12). Life expectancy in Japanese men is longer than that for men in other countries (4), and men under healthy conditions and less comorbidities would have undergone RP in our study.…”
Section: Rp In Elderly Mencontrasting
confidence: 49%
“…With a median follow-up of 50 months, the 5-year bFS was 80.9% in those ,70 years of age and was 77.4% among those Jpn J Clin Oncol 2013;43 (12) 1239 70 years of age (P ¼ 0.217). The 5-year CSS was 99.8% in those ,70 years of age and was 99.5% among those 70 years of age (P ¼ 0.692).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Previous studies were retrospective and had significant bias between the age groups preoperatively. Kunz et al (9) reported that patients aged 70 years had biologically more aggressive and locally advanced tumors significantly more often than those aged ,70 years but that patients aged 70 years had significantly more clinically palpable tumors, higher biopsy Gleason scores and a higher proportion of high-risk disease. Brassell et al (8) reported that an age of 70 years was a significant predictor of biochemical recurrence after RP in multivariate analysis, although they had a statistically significant higher clinical stage, biopsy grade and PSA velocity pre-operatively.…”
mentioning
confidence: 99%
“…Elderly patients may be at even greater risk for aggressive prostate tumors compared to younger men [7,8]. Frequently missed in discussions of PSA screening is the potential reduction in prostate cancer morbidity, including the development of metastatic disease and the potential avoidance of androgen deprivation therapy (ADT).…”
mentioning
confidence: 99%